0142 Longer term physical health and wellbeing in australian gulf war veterans, 20 years after deployment. (21st August 2017) - Kelsall, Helen; Ikin, Jillian; Gwini, Stella; Forbes, Andrew; Sim, Malcolm
Abstract : Background: Ten years after the 1990–1991 Gulf War (GW), Australian veterans were found to have significantly poorer psychological health and some indicators of poorer physical health. Methods: A cohort of GW veterans and matched military comparison group were assessed at baseline (2000–2002) and follow-up (2011–2012), including a 63-item symptom checklist, modified CDC definition of multisymptom illness (MSI), doctor-diagnosed medical conditions since 2001, chronic fatigue and neurological symptom questionnaires. Additional measures e.g. irritable bowel syndrome (IBS) were included at follow-up. Results: From baseline, 715/1, 330 veterans (54%) and 675/1, 449 comparison group (47%) participated at follow-up. Relative to comparison group, GW veterans reported a higher average number of symptoms (ratio of means 1.36, 95% CI 1.24–1.48), higher prevalence of MSI (risk ratio RR 1.60; 1.31–1.95), chronic fatigue RR 1.41 (1.02–1.96), IBS RR 1.64 (1.18–2.27) and 6/40 medical conditions. GW veterans were significantly more likely to report ≥1 RR 1.13 (1.03–1.25) or ≥4 RR 1.32 (1.07–1.64) neuropathic symptoms. From baseline to follow-up, overall, symptom prevalence and MSI increased and remained higher in GW veterans; the gap between GW veterans' and comparison group symptomatology remained unchanged; chronic fatigue prevalence more than doubled in both groups, and there was a non-significantly greater incidence of chronic fatigue in GW veterans. Conclusions: These finding indicate enduring increased health symptoms and longer term adverse physical health outcomes associated with GW service, and highlight the importance of effective detection and management of chronic physical conditions and improved awareness among health practitioners of conditions occurring more commonly in veterans.